2021
DOI: 10.3390/plants10091779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isosteviol on Wheat Seed Germination and Seedling Growth under Cadmium Stress

Abstract: Cadmium (Cd) contamination of agricultural soil has become a serious threat to global food security. The present study highlights the effect of added isosteviol in modulating growth physiology and antioxidant defense systems conferring tolerance against cadmium (Cd) stress in wheat. Wheat growth, chlorophyll content, malondialdehyde (MDA) content of leaves, dehydrogenase activity of root, and antioxidant enzyme activity were determined to get an overview of cellular response in conquering Cd-induced oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Peroxidase is more effective than catalase due to its protective action in removing H2O2 (56). Comparable results were observed in Phaseolus vulgaris (57) and Triticum aestivum (58). Free radicals like O2 and H2O2 accumulation by gamma radiation distressed the system for removing them and caused lipid peroxidation.…”
Section: Discussionmentioning
confidence: 95%
“…Peroxidase is more effective than catalase due to its protective action in removing H2O2 (56). Comparable results were observed in Phaseolus vulgaris (57) and Triticum aestivum (58). Free radicals like O2 and H2O2 accumulation by gamma radiation distressed the system for removing them and caused lipid peroxidation.…”
Section: Discussionmentioning
confidence: 95%
“…Maize Genomics and Genetics 2022, Vol.13, No.3, 1-9 http://cropscipublisher.com/index.php/mgg Under cadmium stress, plants have the effect of "high concentration inhibiting growth and low concentration promoting growth" (Zhang et al, 2019;Wang et al, 2019). In this study, sweet corn varieties with different tolerance were treated with the same concentration of cadmium ion.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the Brassica napus seeds were placed in deionized water (T2) and isosteviol at solution concentrations of 10 −10 (T3), 10 −9 (T4), 10 −8 (T5), 10 −7 (T6), and 10 −6 M (T7) for 24 h. Then, the Brassica napus seeds were removed and placed into Petri dishes with double layers of filter paper (50 grains per dish). According to the results of the previous test [ 16 ], 20 mL of NaCl solution at a concentration of 140 mM was separately added to the above six treatment groups for stress treatment. Seeds soaked in deionized water and stressed without NaCl solution (20 mL of deionized water) were used as the control group (T1), and each group of experiments had 5 replications.…”
Section: Methodsmentioning
confidence: 99%
“…Isosteviol is a tetracyclic diterpenoid with a beyerane skeleton that was first reported by Mosetling and Nes in 1955 [ 14 , 15 ]. Recently, studies have shown that isosteviol has biological activities similar to those of gibberellin in alleviating abiotic stress in plant seedlings [ 16 , 17 ]. For example, Wang et al (2022a) found that soaking seeds in isosteviol (10 −9 ~10 −8 M) could effectively relieve the growth inhibition effect of chromium stress on wheat seedlings, thereby improving the stress tolerance of wheat [ 18 ].…”
Section: Introductionmentioning
confidence: 99%